Development of E-Quiz Based on Liveworksheets for Biodiversity Topic to Train Higher Order Thinking Skills (Journal of Biology Education, 2022)
The research objective was to develop a liveworksheets-based E-Quiz for biodiversity topic to train higher order thinking skills that are both theoretically and empirically valid, reliable, and practically. This study used a 4D model. Theoretical validation was evaluated used the question instrumens, and E-Quiz. The limited trial was carried out by involved 20 10th grade students. The analysis of the empirical validity test used product-moment analysis, reliability test used Cronbach Alpha analysis. The practicality of E-Quiz media was measured used student response questionnaire. Practicality data were analyzed descriptiptively quantitatively. The result of theoretical validation analysis showed that questions developed were very valid with percentage of 99.84% and liveworkhseets-based E-Quiz was declared very valid with percentage 87.60%. The empirical validity test showed that in 1 questions set there were 9 questions declared valid. The reliability test showed that questions developed was declared reliable with high correlation coefficient of 0.717. The practicality test showed that liveworksheets-based E-Quiz was very practical category with percentage 0f 99.17%. Thus, it can be concluded than the E-Quiz based on liveworksheets for biodiversity topic that can be used to train students’ higher order thinking skills based on theoretical validity, empirical validity, reliability, and practicality.